Muscular energetic metabolism study in athletes by 31P-MRS - Santos, M. G.; Gonzalez de Suso, J. M.; Moreno, A.; Cabanas, M.; Arus, C. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The aim of this study was to characterize the muscular reservoirs of phosphorilated energetic components of athletes using 31P-MRS. Methods The sample was formed by 14 elite athletes from the Center for High Sportive Performance (CAR, Sant Cugat del Vallés, Spain). The pattern of the phosphorilated metabolites was measured from the muscle vastus medial by 31P- MRS. Oral supplementation of 20 g of Creatine monohydrate was given during 14 days. Two groups of athletes were formed according to their physical characteristics (weight, height, body mass index, maximum O2 uptake). The first group received a placebo (maltodextrine), while the second group received a diet of creatine supplement. The exercise was performed inside the resonance tunnel with a frequency of 60 RPM with both legs. Results The results showed that significant decrease occurred in phosphocreatine (PCr), inorganic phosphate (Pi) and intracellular pH after supplementation. Discussion/conclusion It was concluded that the exercise performed by the long distance runners recruited in this study, detected by 31P-MRS, reduced the consumption of PCr during exercise due to creatine supplementation diet.